O vencimento da dívida pública cambial influencia a taxa de câmbio? Um estudo econométrico para o brasil no período 2003-2004 (Economia Aplicada, 2007)
The aim of this paper is to test the hypothesis that the exchange rate between the Brazilian real and the US dollar has a different behavior in the periods that precede the liquidation of dollar linked public debt, which could generate an above-normal return to the debt holders. The tests by dynamic regression with dummy variables, the non parametric Mann-Whitney and Wilcoxon tests, and Markov-switching models did not detect an abnormal behavior of the exchange rate in the days that precede the expiration of dollar indexed public debt in 2003 and 2004, rejecting the hypothesis that the expiration of dollar linked public debt is a signalization of abnormal returns on the foreign exchange market. However, that is a change in the volatility of the exchange rate. The Mann-Whitney and Wilcoxon tests and the GARCH model with dummy variables detected a different behavior of the exchange rate on the day of liquidation of dollar linked public debt, after the determination of the exchange rate used to settle the debt. The GARCH model detects an abnormal appreciation of the Brazilian real in comparison with the rest of the years 2003 and 2004. The Markov-switching model did not detect abnormal returns of the exchange rate on the day of expiration of public debt.